Pengembangan Modul Digital Interaktif Perpajakan - Puspita Zandra, Rosy Aprieza; Nurfitriasih, Dyah Metha; Nurindrasari, Diana (Jurnal Pendidikan Akuntansi (JPAK), 2023)
Understanding of taxation has a high urgency, especially for accounting students because tax calculations and reporting are unavoidable in most sectors in Indonesia. Knowledge and understanding of taxation must be possessed by accounting students to prepare themselves to enter the world of work. In addition, learning in lectures experiences segregation from teacher centered to student centered, both synchronously and asynchronously. This requires innovations for systemic improvements to the components of education, especially learning media. The purpose of this study is to examine the development of learning media in the form of interactive digital modules, namely flipbooks in the Taxation course using the ADDIE model. The modules developed have been assessed by material experts, media experts, and tested on a limited basis among internal students who are taking Taxation courses as many as 31 students. The results showed that the feasibility of the material on the interactive digital module was considered sufficient by the material expert validator. Meanwhile, the results of the media expert's validation showed that the interactive digital module was considered good. The results of the limited test on students showed that the interactive digital module was understood. The assessment is on several aspects, namely the presentation of information, the content of cognition and functionality.